2023
DOI: 10.1007/s00239-023-10097-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Supporting That C-to-U RNA Editing Is the Major Force That Drives SARS-CoV-2 Evolution

Abstract: Mutations of DNA organisms are introduced by replication errors. However, SARS-CoV-2, as an RNA virus, is additionally subjected to rampant RNA editing by hosts. Both resources contributed to SARS-CoV-2 mutation and evolution, but the relative prevalence of the two origins is unknown. We performed comparative genomic analyses at intra-species (world-wide SARS-CoV-2 strains) and inter-species (SARS-CoV-2 and RaTG13 divergence) levels. We made prior predictions of the proportion of each mutation type (nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…A total of 94.0% of all As in the SARS-CoV-2 genome have mutated at some time to a G (Table 4), and 70% of total A>G mutations were first observed by the end of September 2020 (Figure 5). The prevalence of C>U and A>G mutations is consistent with the predominant role of host deaminases in causing a significant portion of SARS-CoV-2 mutations [14,17,18,64].…”
Section: Snv Signature Analysissupporting
confidence: 68%
See 2 more Smart Citations

The Mutational Landscape of SARS-CoV-2

Saldivar-Espinoza,
Garcia-Segura,
Novau-Ferré
et al. 2023
IJMS
“…A total of 94.0% of all As in the SARS-CoV-2 genome have mutated at some time to a G (Table 4), and 70% of total A>G mutations were first observed by the end of September 2020 (Figure 5). The prevalence of C>U and A>G mutations is consistent with the predominant role of host deaminases in causing a significant portion of SARS-CoV-2 mutations [14,17,18,64].…”
Section: Snv Signature Analysissupporting
confidence: 68%
“…By mid-April 2020, 70% of all C>U mutations had already been observed (Figure 5). In addition, C>U mutations are the most frequent mutations on average [17], and they have been observed in the largest number of variants, pangolin lineages, and countries (Figure S10). All of this evidence supports the role of C>U mutations as a driving mechanism in the evolution of SARS-CoV-2 [63].…”
Section: Snv Signature Analysismentioning
confidence: 99%
See 1 more Smart Citation

The Mutational Landscape of SARS-CoV-2

Saldivar-Espinoza,
Garcia-Segura,
Novau-Ferré
et al. 2023
IJMS
“…The leading and characteristic mutations of RdRp reported for Omicron are A1892T, I189V, P314L, K38R, T492I, and V57V (Bansal and Kumar, 2022). Subsequent changes in RNA editing and RNA replication errors are the main reasons for the emergence of further mutations (Wang et al, 2023), such as P323L caused by the 14408C>T mutation on RdRp, which results in high mutation rates throughout the rest of the viral genome, despite being predicted to increase the protein stability. In addition, mutations A97V and A185V can alter the secondary structure of a protein (Rahimi et al, 2021).…”
Section: Rdrpmentioning
confidence: 99%
“…The relative mutational impact between RdRp (RNA-dependent RNA polymerase), which introduces errors during replication, and RNA editing enzymes, remains unclear [17][18][19]. Recent studies revealed an enrichment of C-to-U substitutions and, to a lesser extent, A-to-G substitutions in the SARS-CoV-2 genome, offering evidence for RNA editing by APOBEC and potentially by ADAR enzymes [20][21][22][23][24][25]. However, the full extent of this editing can only be conclusively established through experiments using ADAR and APOBEC knock-out cell lines [26,27].…”
Section: Introductionmentioning
confidence: 99%